PALLIATIVE TREATMENT OF ADVANCED CERVICAL CANCER WITH RADIOTHERAPY AND THAI HERBAL MEDICINE AS SUPPORTIVE REMEDY - PESEE , Montien; KIRDPON, Wichit; KIRDPON, Sukachart; PUAPAIROJ, Anucha; PRATHNADI , Pongsiri (The ASEAN Journal of Radiology, 2023)
OBJECTIVE: To evaluate the supportive effect of Thai herbal medicine, Vilac Plus (G716/ 45) on standard radiotherapy in comparison with historic control from the literature reports the results of treatment in stage IIIB-IV cervical cancer. PATIENTS AND METHODS: During the period of March 2003 to June 2005. Thirty patients in advanced cervical cancer stage IIIB-IV with poor performance status were treated by palliative radiotherapy in adjuvant with the Thai herbal tonic solution (Vilac Plus G716/45) daily dose 15-30 ml orally tid, pe as an additional supportive remedy. RESULTS: Thirty cases of patients in advanced cervical cancer stage IIIB-IV with poor performance status, the median age in stage IIIB, IVA, IVB were 50 years (range 41-73 years), 50.5 years (45 years, 58 years), 69 years (67 years, 71 years) respectively. The analysis were being categorized and performed on stages IIIB, IVA, IVA with bladder cancer and IVB reporting in corresponding number of cases/total subject (percentage) were 25/30 (83.33%), 2/30 (6.67%), 1/30 (3.33%) and 2/30 (6.67%) respectively. The median tumor size for stages IIIB, [VA and IVB were 5 cm (range 2-10 cm), 5 cm (4, 6 cm) and 4 cm (2, 6 cm) respectively. The pathological identification had been classified to be squamous cell carcinomas 21/30 (70.00%), adenocarcinomas 7/30 (23.33%), small cell carcinoma 1/30 case (3.33%) and clinically staging IIIB 1/30 case (3.33%). The median time interval between teletherapy and brachytherapy was 22 days (range 7-41 days). Eventually, 84% of the stage IIIB cases were undergone by prolonged gap of more than 2 weeks of time interval between teletherapy and brachytherapy while the rest of the case (16%) received the optimal time gap of treatments. The initial complete response and partial response after 4-6 weeks of radiotherapy were 84% and 16 % respectively. The patterns of failure in stage IIIB revealed in 16 % with residual pelvic diseases (< 6 months), 4% with local pelvic recurrence (> 6 months) and 4% with distant metastases. Median follow-up period in stage IIIB was 22 months (range 2-48 months). Low radiation complications were noted, the severe radiation proctitis (grade 3) was found to be 3.33%. It was notable results in the declined BUN/Cr level in cervical cancer patients with underlying renal insufficiency/chronic renal failure patients treated by palliative radiotherapy and Thai herbal tonic solution as an additional supportive remedy had been observed in 2 cases of stage IIIB and | case of stage IVA with neither surgical intervention nor hemodialysis. CONCLUSION: Our preliminary study in the treatment of advanced cases of Ca. Cervix with palliative radiotherapy and Thai herbal medicine had shown the evidence of initial complete regression of tumour with disappearance of foul smell discharge as high as 84% with low rate of local pelvic recurrence, low distant metastases and low rate of radiation complication. However, the study has a limitation on the number of cases and a short follow up period. Moreover, this treatment modality had shown the benefit on the declination of BUN/Cr level in some cases of those locally advanced stages III B-IV in chronic renal failure caused by chronic ureteric obstruction due to lateral spreading of the cancer pressing on both ureters, without neither surgical intervention nor hemodialysis. The declined BUN/Cr levels were the consequence of the relief of pressure effect on the ureters by the decreasing of the tumour volumes. Palliative radiotherapy with Thai herbal tonic as supportive remedy was safe, cost effective, in addition to the benefit of improval of quality of life without the toxicity of herbal medicine. Therefore, this combination of palliative radiotherapy together with Thai Herbal Medicine would be the alternative option for the palliative treatment of advanced cancer cases with poor performance status or in locally advanced cancer cases. Further studies of increasing number of cases with longer follow up period including multicenters studies should be performed in order to confirm this findings with statistical significant conclusion.